VALIDITAS PENGEMBANGAN LOCAL INSTRUCTIONAL THEORY BERBASIS REALISTIC MATHEMATICS EDUCATION PADA TOPIK APLIKASI TURUNAN - Adevi Murni Adel; Rosmiyati Rosmiyati; Reno Warni Pratiwi; Roza Zaimil; Okviani Syafti; Reni Wijaya (STKIP Pesisir Selatan, 2026)
This study aims to develop a valid Local Instructional Theory (LIT) based on Realistic Mathematics Education (RME) on the topic of Applications of Derivatives. The LIT was developed to create a learning pathway tailored to students’ characteristics in understanding the concepts covered in the Applications of Derivatives material. The development model used in this study is a combination of Plomp’s development model and the development model proposed by Gravemeijer and Cobb. Validation was conducted by five experts, consisting of three content experts, one media expert, and one language expert. The validation instrument was a validation sheet covering content, presentation, language, and graphics. Data were analyzed using quantitative descriptive methods based on average validity scores and qualitative descriptive methods based on the validators’ suggestions. The validation results show that the developed LIT Book received a “very high” rating of 0.82. The Faculty Guide also received a “very high” rating of 0.82. Similarly, the Student Guide received a “very high” rating of 0.81. The results indicate that the LIT textbook, the Faculty Guide, and the Student Guide all based on RME and covering the topic of derivative applications are suitable for use as learning guides for faculty and students.